Mapping a Decade of EFL Writing Instruction Research: A Bibliometric and Systematic Review of Pedagogical Trends, Challenges, and Emerging Directions - Asep Hardiyanto; Sunyono; Hasan Hariri; Agus Suyatna (Universitas Hamzanwadi, 2026)
Research on English as a Foreign Language (EFL) writing instruction has expanded substantially over the last decade, reflecting growing interest in pedagogical innovation, learner-centered instruction, feedback practices, and technology-mediated writing. However, the field remains fragmented, as existing studies often examine isolated instructional strategies, learner populations, or digital interventions without offering an integrated view of its intellectual structure and pedagogical development. This study maps and synthesizes Scopus-indexed research on EFL writing instruction published between 2015 and 2024 through an integrated bibliometric analysis and systematic literature review. A total of 1,030 journal articles were analyzed bibliometrically using Biblioshiny and VOSviewer to examine publication trends, influential authors, source journals, contributing countries, citation patterns, and keyword co-occurrence networks. Following PRISMA 2020 guidelines, 82 empirical studies were further selected for qualitative synthesis. The findings reveal a steady increase in EFL writing instruction research, with accelerated growth between 2021 and 2024. Genre-based, process-oriented, and strategy-based instruction emerged as dominant pedagogical approaches, while sociocultural, cognitive, sociocognitive, and self-regulated learning frameworks commonly informed the field. Persistent challenges include learners’ limited linguistic and rhetorical resources, writing anxiety, low confidence, instructional constraints, and feedback-related difficulties. At the same time, technology-enhanced and AI-assisted writing tools offer opportunities for feedback, collaboration, learner autonomy, and instructional innovation. This review contributes an integrated understanding of EFL writing instruction research by connecting bibliometric patterns with pedagogical and theoretical insights, while highlighting future directions for longitudinal, teacher-focused, contextually diverse, and ethically informed studies on digital and AI-supported writing pedagogy.